2019
DOI: 10.1002/ppul.24346
|View full text |Cite
|
Sign up to set email alerts
|

The impact of mannose‐binding lectin polymorphisms on lung function in primary ciliary dyskinesia

Abstract: Objective Primary ciliary dyskinesia (PCD) is a congenital lung disease that leads to recurrent and chronic lung infection. The resulting inflammation causes lung damage and declines in lung function. Mannose‐binding lectin (MBL) is a first line host defense protein of importance for the innate immunity. Polymorphisms in the MBL gene named MBL2 result in unstable and low functional levels MBL proteins. MBL insufficiency is linked to an increased risk of lung infection and to declines in lung function in patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 29 publications
1
10
0
1
Order By: Relevance
“…Despite MBL deficiency not being the cause of cystic fibrosis, several studies have shown the impact of MBL expression and polymorphisms on the course of CF disease (13). Similar findings were found in patients with non-CF bronchiectasis and in patients with primary ciliary diyskenesia (31)(32)(33). Our data shows that serum levels of MBL were highly related to MBL haplotypes with MBL serum concentrations being unaffected by patients age, gender, and PA status.…”
Section: Discussionsupporting
confidence: 84%
“…Despite MBL deficiency not being the cause of cystic fibrosis, several studies have shown the impact of MBL expression and polymorphisms on the course of CF disease (13). Similar findings were found in patients with non-CF bronchiectasis and in patients with primary ciliary diyskenesia (31)(32)(33). Our data shows that serum levels of MBL were highly related to MBL haplotypes with MBL serum concentrations being unaffected by patients age, gender, and PA status.…”
Section: Discussionsupporting
confidence: 84%
“…Asp+, Aspergillus positive; AspÀ, Aspergillus negative; BALF, bronchoalveolar lavage fluid; CF, cystic fibrosis; HC, healthy volunteers; hMSC, human bone marrowderived mesenchymal stromal cell; ns, not statistically significant. (47). Notably, insufficient amount of mannose-binding lectin has been associated with adverse progression of CF lung disease (18).…”
Section: A B Cmentioning
confidence: 99%
“…Nevertheless, in a report by Pifferi et al, 18 no association was found between MBL2 genotypes and clinical findings other than severity of bronchiectasis in PCD, and they concluded that MBL played a relatively minor role as a disease modifier in PCD. However, in another retrospective longitudinal study by Videbaek K et al 19 which included a larger number of patients with PCD, it was shown that MBL‐deficient patients based on MBL2 genotypes with the A/O genotype ignoring MBL serum measurement were diagnosed earlier and their FEV1 declined significantly faster per year than PCD patients with MBL sufficiency carrying A/A genotype, and they suggested that MBL genotype might be a disease modifier in PCD.…”
Section: Discussionmentioning
confidence: 99%